Facilitated Electron Hopping in Nanolayer Oxygen‐Insensitive Glucose Biosensor for Application in a Complex Matrix. Issue 11 (16th August 2016) - Grattieri, Matteo; Tucci, Matteo; Bestetti, Massimiliano; Trasatti, Stefano; Cristiani, Pierangela
Abstract: Electrochemical experimental evidence of facilitated electron transfer in a sub‐micrometer biosensor is presented. Layer‐by‐layer self‐assembled deposition provides the unique advantage to specifically control the thickness of the biosensors, allowing an oxygen‐insensitive device with a film thickness of 70 nanometers to be obtained. The biosensor is based on a poly(allylamine) osmium redox mediator and glucose 1‐oxidase. The immobilized enzyme contributes to the signal generation through the full biosensor thickness, with no loss of "active enzyme" in the outer layer of the biosensor through reaction with oxygen, as reported in the case of thick redox hydrogels. The application of the biosensor in complex matrices was approached with tests in wastewater. Encapsulation of the biosensor with Nafion® membrane ensured the protection of the enzyme molecules from the external environment, allowing the successful application of the sensor in a complex matrix. Abstract : Hop, skip, and jump ! A nanolayer glucose biosensor with facilitated "electron hopping" is developed through layer‐by‐layer self‐assembled deposition. The controlled structure avoids the loss of "active enzyme" in the outer layer of the biosensor through reaction with oxygen, obtaining an oxygen‐insensitive biosensor. Possible applications of the biosensor in wastewater analysis proposes a new tool for the study bioelectrochemical systems.